Sistem Kehadiran Staf Pengajar dengan Teknologi Tap Card di SDN 164 Karang Pawulang Bandung - Arib Arkan Fadhlullah; Gamma Rizquha W; M. Rafi Yasir; Bariq Azhar M; M. Muslih Attoyibi (Jurnal Riset Multidisiplin Edukasi, 2026)
With the advancement of information technology, digital attendance recording systems are increasingly needed to improve administrative accuracy and effectiveness, particularly in education. SDN 164 Karang Pawulang Bandung currently uses manual attendance recording, which has limitations in terms of speed and accuracy. This project aims to implement an RFID card-based attendance system as an attendance recording solution. The methodology used included initiation, hardware and software design, development, testing, training, and evaluation. The results show that the RFID-based attendance system improves attendance recording accuracy and facilitates real-time data monitoring for school administration, while reducing the potential for manual recording errors. This solution is expected to lead to a more structured and modern school attendance administration system.